If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6n-12=n+
We move all terms to the left:
6n-12-(n+)=0
We add all the numbers together, and all the variables
6n-(+n)-12=0
We get rid of parentheses
6n-n-12=0
We add all the numbers together, and all the variables
5n-12=0
We move all terms containing n to the left, all other terms to the right
5n=12
n=12/5
n=2+2/5
| 1.4=-4.9*x^2 | | b-9+4b=27 | | f/24=4/8 | | 3(4x-7)=5(2x-2)+3 | | -9(x+4)+4=-32 | | 21x()=7 | | 1/2x-1/4x=6-1/8x | | 1.27n+0.44=5 | | 7y+8=7y-9 | | 0.2(10b+6=-4(b-12) | | 6m-4=8m+5-m | | 3(5x+9)=-17+14 | | X=246-(y2) | | 35+o=635 | | 0.5x+1=9+4.5x | | 6.2h=9.3-3.2h | | y/6+y/3=y/5 | | -5(5-3x)+10=4(3x+4)-1 | | -(5x=5)-4+8x= | | 01r-1=0.65 | | 7−c=−15 | | 19y+34=167 | | 4y+6=4y+11 | | 3=6p-11-5p | | 6(x=1)=30 | | 2.1=5.1-0.5x | | 3(y+5)-5=34 | | 8v-6=-78 | | -6x+21+4x=-9 | | 16k-15k=13k | | -4=(-3/4x) | | 7x+7-6×=10 |